IoT and IoE Driven Smart Cities - Nath Sur, Samarendra; Balas, Valentina Emilia; Bhoi, Akash Kumar; Nayyar, Anand; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides detail on applying Internet of Things (IoT) and Internet of Everything (IoE) in smart cities and their design aspects related to physical and network layer models. The authors explore the possibilities of utilizing communication technologies like multi-input multi-output (MIMO), narrow-band IoT (NB-IoT), ultra-reliable low latency communications (URLLC), enhanced mobile broadband (eMBB), and massive machine-type communications (mMTC) for successful implementation of the IoT/IoE. The authors also address the development and advancement in cloud computing to support IoT and IoE. Research on the challenges and future predictions for efficiently implementing and exploring the benefits of smart cities are also explored. The book pertains to researchers, academics, and professionals in the field. Discusses the applicability of Internet of Things (IoT) and Internet of Everything (IoE) for smart cities; Addresses different protocols, networks, and technologies related to the implementation of IoT and IoE for smart cities; Provides a detailed overview on the physical and network layer design and signal processing algorithms related to IoT and IoE.
Introduction -- Section 1: Review on IoT/IoE for Smart Cities -- A comprehensive review on physical layer design for Smart cities -- A comprehensive review on security and privacy aspect for Smart cities -- A comprehensive review on IEEE IoT/IoE standards for Smart cities -- Section 2: IoE Physical Layer Design for Smart Cities -- Analysis of multi antenna signal processing for the realization of IoT/IoE -- Analysis of spectrum management for the realization of IoT/IoE -- Analysis of RF energy harvesting techniques for the realization of IoT/IoE -- Section 3: IoE Network Layer Design for Smart Cities -- Design and signal processing aspect of Wireless Sensor Networks -- Design aspect of Device to Device (D2D), Machine to Machine (M2M) Network -- Vehicular Ad Hoc Networks (VANETs) for IoT -- Section 4: IoE-Intelligent Computing systems for Smart Cities -- Analysis of cloud-based design for the realization of smart cities -- Review on Machine Learning/ deep learning Algorithms for smart cities -- Application of Machine Learning/ deep learning Algorithms for the IoE -- Section 5: IoT/IoE Applications: Smart Cities -- IoT platform for Smart Cities: Requirements and implementation case studies -- Real life case studies on smart cities -- Survey on Research/Implementation Challenges: IoE for Smart Cities -- Conclusion.
Keywords: Cooperating objects (Computer systems).; Telecommunication; Application software; Cyber-Physical Systems; Communications Engineering, Networks; Computer and Information Systems Applications; Internet of things; Smart cities